Estudos de programas nutricionais alternativos na dieta de frangos de corte com o uso do grão inteiro de sorgo - Silveira, Márcia Marques (2014)
The present study aimed to compare three nutritional programs, developed with rations based on whole grain sorghum without tannin, evaluating the growth performance, carcass yield and cuts, gastrointestinal development and the absorption surface of the small intestine of broilers. In total, 1360 broiler chicks, mixed (50:50), with a day-old lineage Hubbard Flex were distributed according to a completely randomized design composed of four treatments and ten replications each, as follows: three programs with whole sorghum grain-based ration (nutrition program with daily adjustment, nutritional program with adjustment every three days and four phases) and a program with ground sorghum grain-based ration (four phases). The variables analyzed were the feed intake; weight gain; feed conversion; viability; eviscerated carcass yield and cuts (chest (full and boned), thighs/drumsticks and wings); chemical composition of the pectoral muscle; relative weight of the small intestine (ID) and gizzard; length, histomorphometry and absorption area ID. Performance variables were submitted to ANOVA. The variables of yield, composition, relative weight of gizzard and ID and ID length were submitted to ANOVA in factorial scheme (4x2). In the variable ID histomorphometry of males applied the ANOVA. Verification of the strength and direction of a linear relationship between the weight of gizzard and intestine weight was made through the Pearson correlation coefficient. Nutrition program with adjustment daily and every three days showed better feed conversion, didn´t affect carcass yield and commercial cuts, promoted an increase in size of the gizzard, which result in further development of the small intestine. It is concluded that the daily feeding programs could be made possible in the poultry industry with the mixture of sorghum grains and concentrates directly on farms running for better logistics and shipping cost of feed.